Increment of mixed convection heat transfer and decrement of drag coefficient in a lid-driven nanofluid-filled cavity with a conductive rotating circular cylinder at different horizontal locations: A sensitivity analysis - Mirzakhanlari, Soroush; Milani Shirvan, Kamel; Mamourian, Mojtaba; Chamkha, Ali J. (Powder technology, 2017)
Since in most industrial rotating equipment, increasing thermal efficiency and reduction of drag has always been subject of interest, in this paper, a 2-D numerical investigation on mixed convection heat transfer and drag coefficient in a lid-driven square cavity filled with Al2O3 Nanofluid is done under the effect of an inner rotating cylinder. To analyze effective parameters on heat transfer and drag coefficient on movable wall, a sensitivity analysis is carried out utilizing the Response Surface Methodology. Simulations are performed for effective parameters of the Richardson number (0.1≤Ri≤10), dimensionless rotational speed (0≤Ω≤5), a/b ratios (0.5≤S≤1), and the Nanoparticle volume fraction (0.00≤Ф≤0.03) with a constant Grashof number of 104. It is found that the mean Nusselt number enhances with Ri number and Ф and decreases with increasing of Ω and S. Additionally, increasing the Ri number and Ω increases the drag coefficient but it reduces as Ф and S increase. The sensitivity analysis results showed that to maximize the mean Nu number and minimize the drag coefficient simultaneously, the effective parameters must be Ω=0, Ri=0.13636, Ф=0.03 and S=0.5. [Display omitted] •A sensitivity analysis is performed to analyze effective parameters on heat transfer and drag coefficient on movable wall.•It is found that the mean Nusselt number enhances with Ri number and Ф.•It is found that the mean Nusselt number decreases with increasing of Ω and S.•To maximize only the mean Nusselt number, the effective parameters are: Ω=5, Ri=10, Ф=0.03 and S=0.5.•To minimize only the drag coefficient the effective parameters are: Ω=0.9899, Ri=0.1, Ф=0.03 and S=1.